Chronology of heterogeneous deposits in the side entrance of Postojna Cave, Slovenia - Ferk, Mateja; Lipar, Matej; Šmuc, Andrej; Drysdale, Russell N.; Zhao, Jian (Acta geographica Slovenica, 2019)
The development of the tourist trail in the side passage Rov Novih Podpisov of Postojna Cave in 2002 exposed an over four metres thick sedimentary succession characterised by horizontal flowstone layers intercalated between fine-grained fluvial sediments, and gravel deposits that record past environmental changes. The time of the flowstone deposition was determined by radiocarbon and uranium-thorium dating techniques. The results yielded three distinctive age groups of flowstone facies of 33 ka, 103 ka and 153 ka. These results also indicate that flowstone deposition has not been limited solely to periods of warm climate, which suggests that environmental conditions during glacial periods in south-western Slovenia supported flowstone deposition.